PENYEDIAAN TRANSPORTASI UMUM MASA DEPAN DI KOTA SEMARANG - Siti Rahma; Dyah Amalia Wijayanti; Ismiyati Ismiyati; Djoko Purwanto (Jurnal Karya Teknik Sipil, 2014)
The increasing number of private vehicles using in Semarang causes a high traffic volume in some primary roadways of the city. It can be seen from the use of official cars vehicle / personal that originally totaled 34,000 vehicles in 2007 to 44,600 vehicles in 2009 (Badan Pusat Statistik Kota Semarang, 2009). The presence of mass public transportation Bus Rapid Transit, which is Trans Semarang, is considered not able to overcome such problem yet. The value of the load factor both BRT corridor I and II were only 20-30%. (Based on research Chairunnisa R, Yenni N, 2010 and Ilham H. Rasyid, Aldila Bachtawar., 2013). The aim of this research is to evaluate public transportation’s performance and to figure out the policy of public transportation that is suitable for the economic condition, and demand from citizens of the city of Semarang. The methods used are analyzing previous research data about public transportation, especially BRT Trans Semarang, and processing primary data in the form of interview survey to citizens. The survey is done in three sub-districts: Ngaliyan, Pedurungan, and Banyumanik. The aspects that are reviewed through the side of effectiveness and efficiency of public transportation are headway, frequency, public transport fares, security, safety, and comfort. According to the result of the research, it is identified that more than 50% of citizens prefer using private vehicles, because the public transportation had not satisfy yet. Therefore, the effort of improving and developing provided public transportation is needed. In this case, the region is divided into two sections journey, namely urban and suburban areas. In the urban areas, can be done by revamping the BRT transport system, the provision of special BRT lane, and the provision of feeder that fits the needs of society. Whereas in suburban areas, public transportation is needed for high speed travel time savings, in addition to reducing the occurrence of traffic congestion on the main roads of the city.